2016
DOI: 10.14687/jhs.v13i3.3917
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and opinions of nursing students on palliative care: A university example

Abstract: Objectives: This study was conducted to determine the level of knowledge of nursing students about palliative care. Methods: The descriptive study was conducted with 324 graduate students who received training at a state university. Data were collected by using a questionnaire prepared by the researchers to determine the students' level of knowledge about palliative care and the notion of death. The analysis was performed using parametric and non-parametric tests on computers. Results: The average age of stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
2
4
0
Order By: Relevance
“…In terms of the knowledge on the need of palliative care, the majority were aware that palliative care is appropriate for metastatic cancer with uncontrolled pain and endstage heart failure. This is similar to a study conducted with nursing students, which found that most of them were aware that palliative care is needed for advanced stage chronic diseases, terminally ill patients, patients with advanced stage chronic diseases, and cancer patients with chronic diseases [14]. However, a recent study reported students wrongly assumed that palliative care is needed in acute postoperative pain as the students were unable to differentiate between pain medicine and palliative medicine [13].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In terms of the knowledge on the need of palliative care, the majority were aware that palliative care is appropriate for metastatic cancer with uncontrolled pain and endstage heart failure. This is similar to a study conducted with nursing students, which found that most of them were aware that palliative care is needed for advanced stage chronic diseases, terminally ill patients, patients with advanced stage chronic diseases, and cancer patients with chronic diseases [14]. However, a recent study reported students wrongly assumed that palliative care is needed in acute postoperative pain as the students were unable to differentiate between pain medicine and palliative medicine [13].…”
Section: Discussionsupporting
confidence: 78%
“…The majority of the students were shown to have an average and above knowledge level on palliative care. The finding is similar to the level of knowledge among physiotherapy students in Nigeria [13] and nursing students in Turkey [14]. This could be attributed by the usage of the same outcome measures and similar experience and the level of study of the participants (Year 4 students), where the more "senior" students are a strong predictor of higher knowledge about palliative care [15].…”
Section: Discussionsupporting
confidence: 69%
“…This fact is also identified in studies exploring educational needs in palliative care for both students and professionals. Indeed, both groups refer to the need for training in these psychosocial aspects of palliative care [ 16 , 23 , 48 , 49 , 71 , 72 , 73 , 74 , 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…This fact suggested the educational need for these aspects in palliative care for both students and nurses, which can be met by conducting training courses on all aspects of palliative care. 53,54 Concerning selected socio-demographic influencing factors, our study suggested that younger age was an influencing factor for knowledge about palliative care. This study suggested that the younger nurses had more knowledge about palliative care compared with older.…”
Section: Discussionmentioning
confidence: 83%